LARVAE OF THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA (CUVIER) FROM THE WEST COAST OF INDIA - Silas, E G (Indian Journal of Fisheries, 2011)
Larvae of the Indian mackerel, Rastrelliger kanagurta (Cuvier) have beenidentified by the author from the plankton of the south west coast of India andthe Laccadive Sea collected during the cruises of R. V. VARUNA. Prolarvaland postiarval sta-ges from the size 1.73 mm to 8.6 mm (T.L.) are describedfrom the graded series present in the collections to highlight the salient featuresduring the larval develc^ment. This account also represents the first descriptionswith illustrations of the mackerel larvae from the west coast of India.The distribution of the larvae, their occurrence in day and night verticaltovra made with tlae Indian Ocean Standard Net, the relative abundance of larvaein the continental shelf and oceanic waters, their abundance latitude-wise, thesize-wise frequency of occurrence of larvae and the Temperature-Salinity, Temperature-Dissolved Oxygen, Saliruty-Dissolved Oxygen relationship to the occurrenceof the larva; from 38 out of 92 stations in the month of May 1964 arealso discussed.